Modulation of Peptide–Graphene Interfaces via Fatty Acid Conjugation. Issue 1 (30th November 2020) - Parab, Atul D.; Budi, Akin; Brljak, Nermina; Knecht, Marc R.; Walsh, Tiffany R.
Abstract: Materials‐binding peptides have the capability to specifically recognize 2D nanomaterials and their modification via covalent attachment of nonnatural moieties offers exciting under‐explored possibilities to tune and exploit this recognition property. Here, an integrated suite of experimental approaches is used to reveal how conjugation of a fatty‐acid chain modifies surface adsorption of a graphene‐binding peptide, P1, achieved using quartz crystal microbalance measurements to access biomolecule adsorption free energies at the aqueous graphene interface, atomic force microscopy to investigate the overlayer morphologies, and circular dichroism spectroscopy to probe peptide secondary structures in the unadsorbed state. To complement these data, replica‐exchange with solute tempering molecular dynamics simulations predict the conformations of these biomolecules in both the surface‐bound and unbound states. Conjugation of the fatty acid dramatically modifies the surface‐adsorbed conformations. However, these conformational changes do not lead to substantial differences in the graphene binding strengths for each of the biomolecules studied, due to enthalpic/entropic compensation arising from changes to the contributions of peptide/graphene, peptide/fatty acid, and fatty acid/graphene interactions. These findings provide a fundamental basis for guiding future modification of materials‐binding peptides to adapt their binding propensities for applications using 2D nanomaterials. Abstract : Through an integrated fusion of experiment with enhanced sampling molecular simulations, substantial differences are revealed in the balance of enthalpic and entropic contributions to graphene binding, for peptides conjugated with fatty acid molecules. These findings provide a critical knowledge base that can guide the rational design of functional graphene bio‐interfaces that can be usefully deployed in devices.